Education to Reduce Food Waste through Bye Waste Social Business - Elzagi, Verliana; Putra, Edy Yulianto; Febiana, Anjela Rini; Yeronica, Fernanda; Eviyani, Estin Rose; Risvi, Hellena; Melissa, Melissa (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2023)
The issue of food waste is very important as it affects various aspects of human life and the surrounding environment. Business ideas on food waste management are important to help people maintain cleanliness and environmental sustainability. Therefore, an e-booklet business idea with the title